Administrative discretion and its limits in the definition of environmental rules in public procurement (Revista Digital de Direito Administrativo, 2023)
Public procurement absorbs a significant part of the Brazilian gross domestic product, highlighting the importance of the State's environmental responsibility as a consumer for the economic effectiveness of environmental sustainability measures. Brazilian Law, in fact, imposes sustainable national development as an objective to be achieved through public procurement. The complexity of the legal system, however, makes the task of defining, in each contract, the applicable environmental standards quite difficult. This article seeks to examine the role of administrative discretion in defining these rules. The limits imposed to administrative discretion by the legal system are researched, as well as the reasoning for discretionary decision-making in the light of the legal principle of proportionality. Some possibilities of discretionary decisions are identified, given different normative grounds for environmental standards. It is concluded that there is a scope for administrative discretion in all the examined situations.